O processo de consentimento livre e esclarecido no uso religioso/ritualístico da Ayahuasca - Valêncio, Luis Felipe Siqueira (2019)
The expansion of the religious / ritualistic use of ayahuasca (psychoactive beverage original from the Amazon region) provided a diverse context of practices, customs and worldviews among the groups that use the beverage. To have access to ayahuasca, people who wish to consume it must undergo an instruction, according to current Brazilian law. The aim of this work was to describe, from a transdisciplinary perspective, how this instruction occurs in twenty groups that use ayahuasca. Field observations and interviews with the use of semistructured script were carried out, which after transcription were submitted to the content analysis technique. This technique allowed us to describe the different instructional models, duration, importance, content, characterization of the instructors, characterization of the visited groups and difficulties found during the process. The instruction is presented as an indispensable stage for the reception of new members in ayahuasca groups, given its function of harm reduction and maximization of benefits.